Urinary bladder augmentation with acellular biologic scaffold—A preclinical study in a large animal model. Issue 2 (29th July 2021) - Pokrywczynska, Marta; Jundzill, Arkadiusz; Tworkiewicz, Jakub; Buhl, Monika; Balcerczyk, Daria; Adamowicz, Jan; Kloskowski, Tomasz; Rasmus, Marta; Mecinska‐Jundzill, Kaja; Kasinski, Damian; Frontczak‐Baniewicz, Malgorzata; Holysz, Marcin; et al.
Abstract: Current strategies in urinary bladder augmentation include use of gastrointestinal segments, however, the technique is associated with inevitable complications. An acellular biologic scaffold seems to be a promising option for urinary bladder augmentation. The aim of this study was to evaluate the utility of bladder acellular matrix (BAM) for reconstruction of clinically significant large urinary bladder wall defects in a long‐term porcine model. Urinary bladders were harvested from 10 pig donors. Biological scaffolds were prepared by chemically removing all cellular components from urinary bladder tissue. A total of 10 female pigs underwent hemicystectomy and subsequent bladder reconstruction with BAM. The follow‐up study was 6 months. Reconstructed bladders were subjected to radiological, macroscopic, histological, immunohistochemical, and molecular evaluations. Six out of ten animals survived the 6‐month follow‐up period. Four pigs died during observation due to mechanical failure of the scaffold, anastomotic dehiscence between the scaffold and native bladder tissue, or occluded catheter. Tissue engineered bladder function was normal without any signs of postvoid residual urine in the bladder or upper urinary tracts. Macroscopically, graft shrinkage was observed. Urothelium completely covered the luminal surface of the graft. Smooth muscle regeneration was observed mainly in the peripheral graft region and gradually decreased toward the center of the graft. Expression of urothelial, smooth muscle, blood vessel, and nerve markers were lower in the reconstructed bladder wall compared to the native bladder. BAM seems to be a promising biomaterial for reconstruction of large urinary bladder wall defects. Further research on cell‐seeded BAM to enhance urinary bladder regeneration is required.